Evaluation and comparison of the tracking performance between NPID Icond controller, NPID controller, and PID controller - Maslan, Mohd Nazmin; Saidin, Iqbal Afiq; Abdullah, Lokman; Yakub, Fitri (Taylor's University, 2023)
Precise positioning and tracking accuracy in machine tools applications are highly demanded in manufacturing sector. The cutting force disturbance is one of the factors that affect the tracking accuracy of the machine tools. The design and selection of the control mechanism for the tools and systems in the manufacturing industry are vital in reducing the disturbance occurrence. This paper presents the performance evaluation of a newly designed controller, namely, nonlinear proportional-integral-derivative controller with conditional integrator (NPID ICond), in terms of the root mean square error and maximum tracking error for an XYZ ball screw drive table. A few comparisons were made with the performance of the other two existing controllers, PID controller and NPID controller. The NPID ICond controller improved the tracking performance of the system by at least 3.172% and 4.139% in terms of RMSE and MTE, respectively. The conditional integrator in NPID ICond controller is proven useful in improving the tracking performance of machine tools application by acting as an anti-windup mechanism.